Recurring large deletion in DRC1 (CCDC164) identified as causing primary ciliary dyskinesia in two Asian patients - Kozo Morimoto; Minako Hijikata; Maimoona A. Zariwala; Keith Nykamp; Atsushi Inaba; Tz‐Chun Guo; Hiroyuki Yamada; Rebecca Truty; Yuka Sasaki; Ken Ohta; Shoji Kudoh; Margaret W. Leigh; et al. (Molecular Genetics & Genomic Medicine, 2019)
Abstract Background Primary ciliary dyskinesia (PCD) is a relatively rare autosomal recessive or X‐linked disorder affecting ciliary function. In the set of causative genes, however, predominant pathogenic variants remain unknown in Asia. Method A diagnosis of PCD was made following a modern comprehensive testing including genetic analysis; targeted resequencing for screening variants, and Sanger sequencing for determination of the breakpoints, with an additional review of databases to calculate the deletion frequency. A multiplexed PCR‐based detection method has also been developed. Results We ascertained a 50‐year‐old Japanese male who had been diagnosed with diffuse panbronchiolitis (DPB), but refractory to macrolide therapy. We reevaluated the case and identified a large homozygous deletion spanning exons 1 to 4 of the DRC1 and determined the breakpoints (NM_145038.4: c.1‐3952_540 + 1331del27748‐bp). In the PCD cohort at the University of North Carolina, we found a female PCD patient of Korean descent harboring the same homozygous deletion. From the Invitae testing cohort, we extracted four carriers of the same deletion among 965 Asian individuals, whereas no deletion was found in the 23,951 non‐Asians. Conclusion We speculate that the DRC1 deletion is a recurrent or perhaps founder mutation in Asians. The simple PCR method could be a useful screening tool.